The Role of North Sumatra MUI Through Empowerment Waqf Al Nuqud in Increasing Micro, Small and Medium Enterprises in North Sumatra - Yahya, Muhammad Faishal; Juliati Nasution, Yenni Samri; Imsar, Imsar (Moneter: Jurnal Keuangan dan Perbankan, 2023)
Micro, Small and Medium Enterprises (MSMEs) are one of the economic units that play an important role in the Indonesian economy. In the process of developing this business, each MSME experienced many obstacles that hindered their production, including the difficulty of obtaining capital loans from conventional BANK. Therefore the MUI of North Sumatra as a government institution which is also the pioneer or manager of Waqf al Nuqud should make this issue a reference for determining optimal programs, especially in managing Waqf al Nuqud, so that the resulting output can touch and help MSMEs in Sumatra. North. The research method used is to use qualitative methods (qualitative research). The purpose of this study was to find out the role of the North Sumatra MUI in improving micro, small and medium enterprises through the empowerment of Waqf al Nuqud. Through the results of the researcher's analysis of the role of the North Sumatra MUI in improving MSMEs through empowering waqf al nuqud, namely 1) Forming a P2WP institution (Center for Productive Waqf Development), with the aim that the management of Waqf al Nuqud can be carried out in a structured way and an institution that is consistent in dealing with these issues, 2 ) Managing Waqaf al Nuqud in the form of Epowerment, including providing capital loans to MSMEs, establishing halalmarts and providing guidance in the form of business management workshops to MSMEs who have been given capital loans.